Effect of Biowaste on the High- and Low-Temperature Rheological Properties of Asphalt Binders - Xuancang Wang; Yuchen Guo; Guanyu Ji; Yi Zhang; Jing Zhao; Hao Su (Advances in Civil Engineering)
The growth of aquaculture has increased the production of oysters. However, the increased oyster shell volume has created serious environmental and recycling problems for the society. In order to study the sustainable utilization of waste oyster shells, asphalt binder of waste oyster shell powder was prepared by using modified asphalt material with waste oyster shells. The microstructure of oyster shell powder was analyzed by scanning electron microscopy experiments. The chemical composition of the asphalt binder was observed by Fourier transform infrared spectroscopy tests. The physical properties of the asphalt binder, including softness, high-temperature performance, and plastic deformation capacity, were initially evaluated through three indicators’ tests on asphalt. A preliminary performance evaluation of the asphalt binder was performed. The high-temperature stability of asphalt binders was evaluated using dynamic shear rheometry. The rutting resistance of the material was evaluated by temperature sweep tests, and the shear deformation resistance of the material was evaluated by frequency sweep tests. Multiple stress creep recovery tests determine the material’s ability to resist permanent deformation. The low-temperature rheological properties were evaluated by bending beam rheology tests. The study found that the waste oyster shell powder is a biomass with a porous irregular petal shape. No new characteristic absorption peaks are formed by mixing with asphalt. And, it can improve the viscosity, thermal stability, and temperature-sensitive properties of the material. It significantly improved the high-temperature rheological performance, rutting coefficient, and recovery elasticity of the material. However, it has little effect on low-temperature rheological performance. This study provides a solid foundation for the effective use of biowaste in engineering materials.